Pengaruh Visual Postingan Instagram pada Campaign “Born This Way” @skingameofficial terhadap Self Esteem - Salsabila Ananda; Daniel Handoko (STIKes Ibnu Sina Ajibarang, 2024)
Utilizing visuals in posts is one of the important things for a brand. Utilizing visual elements in a post is a strategy that companies can use to convey messages that can influence audience attitudes. So the purpose of this study is to determine whether Visual Posts have an influence on Self Esteem. The theory used in this research is the theory of visual elements which includes, color, typography, photography, symbolism. While the Self Esteem theory used includes significance, power, competence and virtue. This research uses quantitative methodology with survey method. The population used in this study were @skingameofficial Instagram followers who had commented on the "Born This Way" campaign post. The data collection technique was carried out by distributing questionnaires to 93 respondents who had been counted. Sampling using the Random Sampling Technique. This research is shown by the average value of respondents' answers to the variable (X) of 4.45, this value is classified as high (Agree) and the average respondent's answer to the variable (Y) of 4.58, which is classified as high (Agree). (Y) of 4.58 which is also dominantly high (Agree). The considerable influence of the Visual Postings Campaign "Born This Way" can also be seen from the value (R) correlation of 0.796 which is said to be high or strong and the R Square value of 0.634 or 63.4% of the effect while the remaining 36.6% of the effect can be seen from the value (R) correlation of 0.796 which is said to be high or strong. and R Square value of 0.634 Or 63.4% effect while the remaining 36.6% is influenced by other things. Visuals in posts are one of the important things for a brand.